Juvenile lupus, cytomegalovirus infection and cardiac tamponade: case report - Levi Coelho Maia Barros; Matheus Eugênio de Sousa Lima; Roseny Marinho Mesquita Pereira; Lia Arcanjo Alves Vasconcelos; Willenne Campelo Rabelo (Sociedade de Pediatria de São Paulo, 2021)
ABSTRACT Objective: To describe a rare case of cardiac tamponade in a pediatric patient with systemic lupus erythematosus (SLE) and cytomegalovirus (CMV) infection, and to discuss the relationship between these morbidities, the diagnostic approach, and the possible treatments. Case description: A 9-year-old girl presented to the emergency department with severe dyspnea, muffled heart sounds, jugular vein distention, hemodynamic instability, and intense pallor. She had previously been followed up at the outpatient clinic for a six-month history of mild respiratory distress, polyarthritis, fever, and various cutaneous manifestations. Doppler echocardiogram revealed pericardial effusion. The patient was submitted to pericardiocentesis followed by water seal pleuropericardial drainage, with no complications. The investigation continued, with fulfillment of clinical and laboratory SLE criteria plus CMV antigenemia of 15/200,000 cells. Medications to control CMV infection and SLE were then initiated, with good clinical and laboratory response. Comments: Pediatric SLE commonly manifests in a more severe form, accounting for high morbimortality. Cardiac tamponade could be one of the first manifestations of SLE, which can also be precipitated by infectious agents, such as CMV, leading to diagnostic confusion and misleading the treatment. Changes in therapeutics must also be considered in the presence of both conditions. This study presents a juvenile SLE case aggravated by a CMV infection with the unusual manifestation of cardiac tamponade.%